Africa : The Road to Opportunity - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, remarked that the past-quarter century has to count as the most successful 25 years in history in the fight against poverty. The one region that has so far been conspicuously left behind by that progress is Sub-Saharan Africa. The people of Africa are hard at work building a more hopeful future for their continent. There is no shortage of energy, ambition, or entrepreneurial spirit. What are most severely lacking are resources to support good plans and good ideas. For Africa and the poorest countries in the world a critical source of development funding comes from the International Development Association or IDA. France has been a leader in IDA in the past. The World Bank has responded with an ‘Africa Action Plan.’ Wolfowitz briefly discussed four key areas of focus: Education, Health, Private Sector Development, and Infrastructure.